Analisis Fungsi Kepemimpinan Terhadap Kepuasan Kerja Pada Kinerja Pegawai Dinas Perindagkop Dan UMKM Kabupaten Bandung Barat - Yan Rohaeni; Ester Manik; Aan Hardiyana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This study aims to determine the effect of leadership functions on job satisfaction. Theoretically, the leadership function divided into 3 (three), namely the instruction function, delegation function, and control function. The research method used is the quantitative verification method. The sample used is an employee at the Department of Industry and Trade and SMEs in West Bandung Regency as many as 90 employees. Data analysis techniques using path analysis. The results of the study prove there is an influence of the leadership function on job satisfaction by 52.0%.